Contemporary economic problems 1977 - Fellner, William; American enterprise institute for public policy research (Washington, D.C.: American Enterprise Institute, 1977)
The studies are directed at employment policy and inflation at a crucial aspect of fiscal policy and at demand-management policies in general, including both monetary and fiscal policy, with a focus on the pursuit of desirable targets for total effective demand.
rpm 05/05/2017
Loans
Keywords: Inflation (Finance) $1 (BUnited Statess; Fiscal policy $1 (BUnited Statess; United States $1 (BEconomic policys; United States $1 (BEconomic conditions $1 (B1971-s; United States